Simulation experiment of acid rain leaching in different media vadose zones polluted by copper - Xue Xia; Zhihui Qu; Xin Song; Biao Yu; Wei Du (Desalination and Water Treatment, 2025)
The leaching process of copper in the polluted medium and the pollution risk to the underground environment under the conditions of acid rain (pH 5.02 ± 0.02), natural rain (pH 6.8 ± 0.02), and different rainfall (moderate rain, heavy rain, and rainstorm) were examined through simulated column experiments with fine sand and medium sand as the vadose zone media. The results showed that Cu²⁺ release underwent three distinct phases: saturation phase, rapid release, and gentle release. Under acid rainfall leaching (pH 5.02 ± 0.02), the lowered pH of the vadose zone media enhanced copper migration. Increased rainfall volume significantly accelerated both the release rate and cumulative Cu²⁺ release, with the highest cumulative release observed under rainstorm conditions. Furthermore, lithological differences between media types influenced copper adsorption capacity, as fine sand exhibited stronger adsorption and lower leaching efficiency compared to medium sand.